(untitled) (Castilla. Estudios de Literatura, 2021)
This essay studies the interpretation of the figure and the work of Benito Pérez Galdós, especially in the first series of the Episodios Nacionales, during the Second Republic and the Spanish Civil War (Republican side). In particular, it is revealed how the myth of the republican and popular writer is built in himself and in his links with the symbolic pattern that allows considering the war as the Second War of Spanish Independence.